EVALUATION OF ANTI-CANCER ACTIVITY OF TRIDAX PROCUMBENS LEAF EXTRACTS ON A549 AND Hep G2 CANCER CELL LINES - P, Vishnu Priya; Rao A, Srinivasa (Asian Journal of Pharmaceutical and Clinical Research, 2015)
ABSTRACT Objective: Evaluation of anticancer activity of various extracts of leaves of Tridax procumbens by 3-(4,5-dimethyl-thiazole-2-yl)-2,5-diphenyl tetrazolium bromide (MTT) assay, and trypan blue dye exclusion assay against A549 (human lung cancer cell line), Hep G2 (human liver carcinoma cell line). Methods: In vitro anticancer activity of ethanol, acetone, and aqueous leaf extracts of T. procumbens was evaluated on selected cancerous cells lines by MTT assay and trypan blue dye exclusion assay. MTT assay is based on the capacity of mitochondrial enzymes of viable cells to reduce the yellow soluble salt MTT to purple blue insoluble formazan precipitate which is then quantified spectrophotometrically at 570 nm. Trypan blue assay is based on staining of cells. Cells are then counted using hemocytometer under the microscope, non-viable cells were stained blue, viable cells remain unstained. Results: The aqueous leaf extract of T. procumbens has not shown any anticancer activity. However, potent anticancer activity was shown by the acetone and ethanol leaf extracts of T. procumbens on A549 (human lung cancer cell line), Hep G2 (human liver carcinoma cell line). Conclusion: The anticancer medicinal plant i.e., T. procumbens was studied by in vitro evaluation methods i.e., MTT assay and trypan blue exclusion assay. The acetone and ethanol leaf extract of T. procumbens have shown potent anticancer activity on selected cancerous cell lines. More efforts are needed to explore potent anticancer plants from the mother earth and save humans around the world from cancer. Keywords: Anticancer activity, Tridax procumbens, 3-(4,5-dimethyl-thiazole-2-yl)-2,5-diphenyl tetrazolium bromide assay, Trypan blue exclusion assay, A549, Hep G2, Ethanol, Acetone, Aqueous.